METODE PENDIDIKAN DAN PENGAJARAN YANG DITERAPKAN OLEH NABI MUHAMMAD SAW - Khumaidi, M. Wisnu; Singgih, Muhammad (STKIP PGRI Bandar Lampung, 2021)
Each educational process requires a strategy in delivering the learning curriculum that will be learned to students. He gives too many goods of examples in everything, including how if a teacher conveys knowledge to his students. Of all the learning methodologies taught by the Prophet Muhammad, there is one core thing that becomes a guideline for every teacher or educator, namely civility. Conscientiousness is the source of examples from educators to students. Because a simple example of what students get is, of course, the educator. There are three concrete and simple things that students can see and model from their teachers, namely polite, compassionate and simple. There are many methods that can be learned also taken from the Prophet Muhammad. But in this paper, the author will only discuss 14 learning methods, Namely Exemplary Methods, Training and Familiarizing Methods, Giving Guidance and Direct Descriptions Methods, Explaining with Parables Methods, Gentle Teaching Methods, Methods of Giving Punishment and Rewards, Question and Answer and Discussion Methods, Presenting Stories that Contain Lessons Methods, Phasing and Repetition Methods, Situational and Conditional Methods, Advice Methods, Problem Solving Methods, Direct Practice Experience Methods, Communicating According to Children's Ratio Ability Methods.